Early Epcoritamab Administration Revives CAR‐T Cells in Relapsed/Refractory B‐Cell Lymphomas - Kensuke Yanashima; Yoshiki Furukawa; Midori Ishii; Shintaro Kinoshita; Yasuharu Hamano; Naoki Watanabe; Yutaka Tsukune; Hajime Yasuda; Jun Ando; Miki Ando (eJHaem)
ABSTRACT Background Bispecific antibodies are effective for relapsed/refractory B‐cell lymphoma patients even after CAR‐T therapy. Methods Peripheral blood CAR‐T kinetics and functional analysis in vivo were carried out pre‐ and post‐epcoritamab infusion in B‐cell lymphoma patients relapsing after CAR‐T therapy. Results CAR copy numbers spiked at relapse and rose again following epcoritamab administration. Expression levels of CAR‐T exhaustion markers did not increase, whereas perforin and granzyme B expression increased after epcoritamab induction. Conclusion Early epcoritamab administration without cytotoxic agents at relapse after CAR‐T therapy revives CAR‐T cell numbers and cytotoxicity, which may potentially lead to favorable clinical outcomes.